2021
DOI: 10.1007/s00787-021-01727-4
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia polygenic risk is associated with child mental health problems through early childhood adversity: evidence for a gene–environment correlation

Abstract: Previous studies have shown that schizophrenia polygenic risk predicts a multitude of mental health problems in the general population. Yet it is unclear by which mechanisms these associations arise. Here, we explored a possible gene–environment correlation in the association of schizophrenia polygenic risk with mental health problems via childhood adversity. This study was embedded in the population-based Generation R Study, including N = 1901 participants with genotyping for schizophrenia polygenic risk, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
(97 reference statements)
1
8
1
Order By: Relevance
“…The current study extends the relationship between SZ-PRS and CM to early adulthood and finds evidence of a role as mediator of genetic risk for CM. Moreover, the proportion of the effect of SZ-PRS on PLE mediated by CM in our study is much higher compared to that for emotional and cognitive problems reported by Bolhuis et al [ 22 ]. These findings are consistent with a pleiotropic influence of schizophrenia genes.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The current study extends the relationship between SZ-PRS and CM to early adulthood and finds evidence of a role as mediator of genetic risk for CM. Moreover, the proportion of the effect of SZ-PRS on PLE mediated by CM in our study is much higher compared to that for emotional and cognitive problems reported by Bolhuis et al [ 22 ]. These findings are consistent with a pleiotropic influence of schizophrenia genes.…”
Section: Discussioncontrasting
confidence: 83%
“…From that perspective, the observation that CM is also associated with SZ-PRS in two independent, population-based, cohorts is very relevant. Previous research already reported a link between SZ-PRS and CM, with an indirect influence on emotional, attention, and thought problems in children [ 22 ]. The current study extends the relationship between SZ-PRS and CM to early adulthood and finds evidence of a role as mediator of genetic risk for CM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Furthermore, a prospective birth cohort (Generation R) of 1901 participants found schizophrenia PRS to be associated with maternal reports of childhood adversity (OR = 1.08; 95% CI = 1.02, 1.15; P = .01) which the authors replicated in the ALSPAC cohort (OR = 1.02; 95% CI = 1.01, 1.03; P = .001). 44 Further analyses demonstrated that this association was driven by childhood adversities occurring before the age of 5 years (OR = 1.20; 95% CI = 1.05, 1.36; P < .01). A study of 5947 participants from a university student population (age 18–22) found that schizophrenia PRS predicted a report of previous trauma, although the study is limited by its retrospective nature and the lack of information on the timing of the trauma.…”
Section: Resultsmentioning
confidence: 94%
“… 46 Finally, 2 clinical studies 47 , 48 assessed the relationship between global childhood adversity and schizophrenia PRS in their control samples and both found positive associations, although only one was statistically significant. 44 These studies are discussed further in the “Clinical Studies” section.…”
Section: Resultsmentioning
confidence: 99%